Stres Akademik dan Strategi Koping Siswa SMA dalam Fase Prapeminatan: Studi Metodologi Campuran - Hidayat, Taufik; Efendi, Agus; Musadad, Akhmad Arif (Buletin Riset Psikologi dan Kesehatan Mental, 2025)
This study measured academic stress levels and identified coping strategies among students at a senior high school in Surakarta City using a convergent parallel mixed-methods design. Quantitative data were collected from 130 students through the Student Life Stress Inventory (SLSI), while qualitative data were obtained from interviews with 1 guidance and counseling teacher and 4 students. The result shows that 23.1% students experience high stress. Qualitative findings reveal that uncertainty in choosing an academic specialization is the primary stressor, leading to cognitive, emotional, physical, and behavioral disturbances. Students address these challenges using emotion-focused coping, avoidance, distraction-based, peer social support, and problem-focused coping strategies. This study highlights the importance of developing interventions that enhance students’ adaptive stress-management capacities during the pre-specialization phase.